Mastering the Art of War: How Patterns of Gameplay Influence Skill in Halo - Huang, Jeff; Zimmermann, Tom; Nagappan, Nachi; Harrison, Charles; Phillips, Bruce (Proceedings of the International Conference on Human Factors in Computing Systems (CHI 2013), 2013)
How do video game skills develop, and what sets the top players apart? We study this question of skill as measured by a rating generated from repeated multiplayer matches called TrueSkill. Using these ratings from 7 months of games from over 3 million players, we look at how play intensity, breaks in play, skill change over time, and other titles affect skill. These analyzed factors are then combined to model future skill and games played; the results show that skill change in early games is a useful metric for modeling future skill, while play intensity explains eventual games played. The best players in the 7-month period, who we call "Master Blasters", have varied skill patterns that often run counter to the trends we see for typical players. The data analysis is supplemented with a 70 person survey to explore how players' self-perceptions compare to the gameplay data; most survey responses align well with the data and provide explanations for the observed behavior. Finally, we wrap up with a discussion about hiding skill information from players, and implications for game designers.